2019
DOI: 10.1515/zpch-2019-1427
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Ginger Oil in Water Nanoemulsion Using Phase Inversion Composition Technique: Effects of Stirring and Water Addition Rates on their Physico-Chemical Properties and Stability

Abstract: Ginger oil in water (O/W) nanoemulsions, were produced using phase inversion composition method and Tween 80, as emulsifier. Effects of processing parameters namely, stirring rate (100 to1000 rpm) and water addition rate (1–10 mL/min) were evaluated on the physico-chemical, morphological, antioxidant and antimicrobial properties of the prepared O/W nanoemulsions using response surface methodology (RSM). Results indicated that well dispersed and spherical ginger nanodroplets were formed in the nanoemulsions wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…The ginger oil, as per literature, typically show characteristic peaks of O—H stretch (broad, strong) and C—H asymmetric stretch around 3000–2900 cm −1 , C O stretch at 1640 cm −1 , 1377 owing to CH 3 bond stretch and asymmetric angular deformation of = CH 2 . In addition to that some smaller peaks around 1250–1100 cm −1 are attributed to = CH 2 of vinyl group ( Divya et al, 2017 , Farshbaf-Sadigh et al, 2021 , Kalhoro et al, 2022 , Visani et al, 2017 ) which is in good agreement with current studies. The intensities of peak appear in the spectra are small considering the lower concentrations of oil and NS used.…”
Section: Resultssupporting
confidence: 92%
“…The ginger oil, as per literature, typically show characteristic peaks of O—H stretch (broad, strong) and C—H asymmetric stretch around 3000–2900 cm −1 , C O stretch at 1640 cm −1 , 1377 owing to CH 3 bond stretch and asymmetric angular deformation of = CH 2 . In addition to that some smaller peaks around 1250–1100 cm −1 are attributed to = CH 2 of vinyl group ( Divya et al, 2017 , Farshbaf-Sadigh et al, 2021 , Kalhoro et al, 2022 , Visani et al, 2017 ) which is in good agreement with current studies. The intensities of peak appear in the spectra are small considering the lower concentrations of oil and NS used.…”
Section: Resultssupporting
confidence: 92%
“…Numerous studies have shown that the antioxidant and free radical scavenging action of phenolic compounds (e. g., flavonoids, phenolic acids) found in plant essential oils were primarily determined by the number and positions of the hydrogen‐donating hydroxyl groups on the aromatic ring of the phenolic molecules. Farshbaf‐Sadigh et al (2021) [28] reported a similar functional group in GEO. Interestingly, as shown in (Figure 4B), the FTIR spectrum of GEO‐CS has overlapped spectrum profiles with the strong band shifting towards a lower wavenumber of 1013 cm −1 for all the nanobactericides, indicating that the GEO was successfully encapsulated into the chitosan nanoparticles and TPP [29] .…”
Section: Resultsmentioning
confidence: 90%
“…The Fourier Transform Infra-Red spectrum was recorded from 550–4000 cm −1 , as displayed in Figure 2 b. Plenty of functional groups were detected, such as OH bonds, COC, C-C stretch, C=O stretch, and OH stretch [ 25 ]. Detailed information about the peaks, wavelength, and functional groups was tabulated in Table 2 .…”
Section: Resultsmentioning
confidence: 99%